PERAN PENDIDIKAN DISIPLIN DALAM MENINGKATKAN SIKAP TANGGUNG JAWAB SISWA STUDI KASUS DI MADRASAH ALIYAH SALAFIYAH SYAFI’IYAH TEBUIRENG JOMBANG - Salim, M. Nur; Irsyad, Mohammad; Syamsudin (EL-Islam, 2023)
Abstrac: Indonesia not only prioritizes IQ but EQ is also a priority in building a virtuous society. EQ can be achieved one of them with moral education whose domain touches on the morals of learners. One way in shaping the morals of learners is through disciplined moral education. Discipline moral education itself acts as the first gateway in the entry of moral education among learners because this discipline is a form of obedience as well as respect for the rules and advice of teachers in Madrasah. The fruit of disciplined education is the growing attitude of responsibility to students. The purpose of this study is 3, namely: (1) Knowing from disciplined education, (2) Knowing the role of disciplined education in improving attitudes of responsibility, (3) Knowing supporting actors and inhibiting disciplined moral education in improving attitudes of responsibility. This type of research uses case studies . This research is included in qualitative research with a background in Madrasah Aliyah Salafiyah Syafi’iyah Tebuireng Jombang. This study analyzed several things related to the Role of Disciplined Moral Education in Improving Student Attitudes of Responsibility. The data obtained from this study is the result of observations, interviews and documentation that are then analyzed and drawn conclusions. Based on the research, it was obtained that disciplined moral education uses teaching methods, transparency and supervision. Disciplined education plays a role in improving student responsibility attitudes. As for the supporting factors and obstacles there are internal and external.